Predicting Deviant Behaviors in Sports Using the Extended Theory of Planned Behavior - Kang, Sangwook; Kim, Inwoo; Lee, Keunchul (Frontiers in Psychology, 2021)
The purpose of the present study was to examine youth athletes’ deviant behaviors using the Extended Theory of Planned Behavior and impulsivity. Five hundred thirty-six middle and high school athletes in South Korea completed a set of questionnaires measuring attitude, subjective norms, perceived behavioral control, intention, ethical obligation, and impulsivity. SEM (Structural Equation Model) analysis revealed that the extended theory of planned behavior model is adequate to explain deviant behaviors in sports. Further, the underlying intentions motivating athletes’ deviant behaviors in sports were significantly predicted by perceived behavioral control and moral obligation. Findings also suggested that intention for deviant behaviors in sports more readily manifests as an actual act when impulsivity scores are high. Theoretical contributions and practical implications are addressed in the discussion section.